The Complicated Evolutionary Diversification of the Mpeg-1/Perforin-2 Family in Cnidarians - Walters, Brian M.; Connelly, Michael T.; Young, Benjamin; Traylor-Knowles, Nikki (Frontiers in Immunology, 2020)
The invertebrate innate immune system is surprisingly complex, yet our knowledge is limited to a few select model systems. One understudied group is the phylum Cnidaria (corals, sea anemones, etc.). Cnidarians are the sister group to Bilateria and by studying their innate immunity repertoire, a better understanding of the ancestral state can be gained. Corals in particular have evolved a highly diverse innate immune system that can uncover evolutionarily basal functions of conserved genes and proteins. One rudimentary function of the innate immune system is defense against harmful bacteria using pore forming proteins. Macrophage expressed gene 1/Perforin-2 protein (Mpeg-1/P2) is a particularly important pore forming molecule as demonstrated by previous studies in humans and mice, and limited studies in non-bilaterians. However, in cnidarians, little is known about Mpeg-1/P2. In this perspective article, we will summarize the current state of knowledge of Mpeg-1/P2 in invertebrates, analyze identified Mpeg-1/P2 homologs in cnidarians, and demonstrate the evolutionary diversity of this gene family using phylogenetic analysis. We will also show that Mpeg-1 is upregulated in one species of stony coral in response to lipopolysaccharides and downregulated in another species of stony coral in response to white band disease. This data presents evidence that Mpeg-1/P2 is conserved in cnidarians and we hypothesize that it plays an important role in cnidarian innate immunity. We propose that future research focus on the function of Mpeg-1/P2 family in cnidarians to identify its primary role in innate immunity and beyond.